2019
DOI: 10.1093/neuros/nyz508
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Complications, Functional Outcome, and Morbidity in a Large Cohort Treated With Flow Diversion

Abstract: BACKGROUND A dramatic improvement in obliteration rates of large, wide-necked aneurysms has been observed after the FDA approved the Pipeline Embolization Device (PED) in 2011. OBJECTIVE To assess the predictors of complications, morbidity, and unfavorable outcomes in a large cohort of patients with aneurysms treated with PED. METHODS A retrospective chart re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 38 publications
4
39
1
Order By: Relevance
“…The PUFS study demonstrated a 180-day aneurysm occlusion rate of 73.6% 15. We reported a 28% rate of postdeployment angioplasty, higher than that recently reported for Pipeline (5.6%) 16. This probably reflects our extremely low threshold for performing angioplasty whenever suspecting incomplete FD apposition on VasoCT, given the demonstrated role of malapposition in delayed aneurysm healing 17.…”
Section: Discussioncontrasting
confidence: 45%
“…The PUFS study demonstrated a 180-day aneurysm occlusion rate of 73.6% 15. We reported a 28% rate of postdeployment angioplasty, higher than that recently reported for Pipeline (5.6%) 16. This probably reflects our extremely low threshold for performing angioplasty whenever suspecting incomplete FD apposition on VasoCT, given the demonstrated role of malapposition in delayed aneurysm healing 17.…”
Section: Discussioncontrasting
confidence: 45%
“…However, thromboembolic events due to the large metal coverage area are also documented and are not entirely mitigated, even with antiplatelet therapy. 3 The ideal characteristics of a flow diverter include optimal pore density and good wall apposition to achieve flow stagnation in the aneurysm, 4 lower overall implant thickness profile to improve endothelial coverage (scaffolding of the parent vessel and aneurysm neck), and low thrombogenic profile to mitigate thrombogenic complications, among other attributes. 5 6 The Pipeline Embolization Device has demonstrated progressive and complete aneurysm occlusion in several large clinical trials including Pipeline for Uncoilable or Failed Aneurysms (PUFs) 7 8 and more recently the Prospective Study on Embolization of Intracranial Aneurysms with the Pipeline Device (PREMIER).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 5% of cases exhibited incomplete PED deployment and required balloon dilatation in this study. Postoperative stent migration, in-stent stenosis, and perforator infarct are also other issues worth considering ( 14 ), and some patients even presented ischemic events after a long follow-up period (>1 year) ( 15 ). Therefore, a flow diverter may not be the first choice for treatment of acute ruptured aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…New antiplatelet drugs, such as cangrelor, which presents a fast and reliable onset of action and reversible platelet inhibition without evidence of resistance, may be a suitable alternative to oral antiplatelet drugs in the acute phase of SAH ( 31 ). The intracranial hemorrhagic complication rate was ~8% in patients who underwent stent-assisted coiling for acutely ruptured IAs ( 32 ); therefore, EVD placement before initiating antiplatelet medication is recommended to avoid hemorrhage ( 14 ). The overall incidence of ischemic complications was 5% ( 33 ), and the incidence of in-stent stenosis ranged from 3.5 to 10% for IAs with flow diversion ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%